Trial by fire [compact disc, unabridged] - Jance, Judith A. (Jance, Judith A. Ali Reynolds mysteries., 2009)
Taking a media relations position with the Yavapai County Police Department, former television journalist Ali Reynolds investigates a subdivision fire and the identity of an injured amnesiac woman, a case that unleashes a family drama and a remorseless killer.